Undergraduates’ Perspectives on Promoting Pleasure Reading Facilities in University Libraries: A Case Study - Perera, K.K.N.L.; Somaratna, Sajeewanie D. (Sri Lanka Library Association, 2024)
Pleasure reading refers to free, voluntary, and non-goal-oriented reading that provides enjoyment or pleasure to the reader. The promotion of pleasure reading is not typically considered a priority in most university libraries. However, recent studies strongly suggest that pleasure reading can have significant, positive impacts on the overall performance of university library users. This study presents undergraduates' perceptions of pleasure reading facilities at the main library of the University of Colombo, as well as their expectations regarding the promotion of these facilities. The results of this study demonstrate a significant population of pleasure readers with diverse reading habits. Most pleasure readers are frequent readers (74.6%, n=209). Novels are the most popular type of reading material (77.5%), followed by non-fiction and short stories. Realistic fiction (33.3%) is the most popular genre among them, followed by fantasy and mystery. A majority of pleasure reading undergraduates have a very positive perception of the benefits of pleasure reading. The three most accepted benefits of pleasure reading were; pleasure reading helps to relax, gives enjoyment and helps to escape from routine work. Most of the participants believe that the promotion of pleasure reading should be a priority for a university library. Among all the facilities related to pleasure reading at the Main Library of the University of Colombo, most of the readers have rated the suitable library environment and the availability of a supportive staff. Pleasure readers prioritize suggested initiatives such as displaying new arrivals and implementing a Readers' Advisory Service to promote pleasure reading in the library.
Keywords: Pleasure reading; Recreational reading; University libraries; Leisure reading